Penguatan Lembaga DPD Melalui Amandemen Ulang Lembaga MPR - Jamaludin Ghafur (Fakultas Hukum Universitas Islam Indonesia, 2007)
The inclusion of Regional Representatives Council (DPD) in the parliament, side by side with House of Representatives (DPR), suggests that the parliamentary system applied in Indonesia is bicameral system, since there are two bodies within this parliament. However, considering that People’s Consultative Assembly (MPR) is not a joint session between DPR and DPD but rather an independent body with independent authorities, can be said accordingly that Indonesian parliamentary system is a “grey” system stands between bicameral and tricameral system.